Investigation of graphene-coated Ag/AgCl electrode performance in surface electromyography measurement - Veysel Alcan; Ersan Harputlu; Cumhur Gökhan Ünlü; Kasim Ocakoğlu; Murat Zinnuroğlu (Biosensors and Bioelectronics: X, 2022)
Conventional silver-silver chloride (Ag/AgCl) electrodes are widely used for recording surface electromyography (sEMG) with a conductive gel. However, for long-term sEMG recording, the gel has some disadvantages that cause high impedance. Therefore, the dry electrodes have been alternatively purposed to overcome these disadvantages. Recently, the nanomaterial-based dry electrodes have been developed for long term electrophysiological signal recording. In the present study, we aimed to develop a graphene-coated Ag/AgCl electrode for long-term recording. We transferred single layer graphene (SLG) on the Ag/AgCl electrode surface by using chemical vapor deposition and confirmed this process by Raman scattering spectroscopy and scanning electron microscopy. We then compared the graphene-coated Ag/AgCl and conventional Ag/AgCl electrodes by evaluating median motor nerve conduction studies (mNCS) and their impedance. The charge transfer resistance (Rct) for the Ag/AgCl electrode (4170 Ω) was much higher than graphene-coated Ag/AgCl electrode (Rct = 24.6 Ω). For median mNCS measurements without gel, the graphene-coated Ag/AgCl electrode provided a better amplitude of distal and proximal compound muscle action potential (28.3 mV and 25.8 mV, respectively) than the Ag/AgCl electrode (21.8 mV and 20.9 mV, respectively). Consequently, the present study suggests promising results in terms of the usability of graphene-coated Ag/AgCl electrodes for long-term monitoring and wearable systems applications of sEMG. In future studies, we aim to investigate clinical applicability of graphene-coated sEMG electrodes that include extended clinical settings and larger study population.